Assisted and resisted sprint training in swimming - Girold, S.; Calmels, P.; Maurin, D.; Milhau, N.; Chatard, J. C. (The Journal of Strength and Conditioning Research, 2006)
This study was undertaken to determine whether the resisted-sprint in overstrength (OSt) or the assisted-sprint in overspeed (OSp) could be efficient training methods to increase 100-m front crawl performance. Thirty-seven (16 men, 21 women) competition-level swimmers (mean ± SD: age 17.5 ± 3.5 years, height 173 ± 14 cm, weight 63 ± 14 kg) were randomly divided into 3 groups: OSt, OSp, and control (C). All swimmers trained 6 days per week for 3 weeks, including 3 resisted or assisted training sessions per week for the groups OSt and OSp respectively. Elastic tubes were used to generate swimming overstrength and overspeed. Three 100-m events were performed before, during, and after the training period. Before each 100-m event, strength of the elbow flexors and extensors was measured with an isokinetic dynamometer. Stroke rate and stroke length were evaluated using the video-recorded 100-m events. In the OSt group, elbow extensor strength, swimming velocity, and stroke rate significantly increased (p < 0.05), while stroke length remained unchanged after the 3-week training period. In the OSp group, stroke rate significantly increased (p < 0.05) and stroke length significantly decreased (p < 0.05) without changes in swimming velocity. No significant variations in the C group were observed. Both OSt and OSp proved to be more efficient than the traditional training program. However, the OSt training program had a larger impact on muscle strength, swimming performance, and stroke technique than the OSp program.